2015
DOI: 10.1186/s13018-015-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of bone-defect repair by using A-W MGC loaded with BMP2 and triple point-mutant HIF1α-expressing BMSCs

Abstract: BackgroundThe goal of this study is to explore the effects of A-W MGC (apatite-wollastonite magnetic bioactive glass-ceramic) loaded with BMP2 (bone morphogenetic protein 2)- and HIF1αmu (hypoxia-inducible factor 1 mutation)-expressing BMSCs (bone marrow mesenchymal stem cells) on the bone defect repair.Methods(1) BMSCs were infected with viral solution containing BMP2 and HIF1αmu with the best MOI (multiplicity of infection). The efficiency was observed via hrGFP (human renilla reniformis green fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that a series of specific molecules were released into the damaged area and enter the circulatory system when bones are damaged, and then the BMSCs from the injured tissue and the circulatory system migrated to the damaged site and differentiate into specific tissues [22]. BMSCs are directly involved in fracture healing [23]. To further explore whether the pretreatment of LIPUS will have beneficial effects on the migration of exogenous BMSCs to the bone defect area in vivo, this study successfully established an animal femoral defect model that could simulate fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a series of specific molecules were released into the damaged area and enter the circulatory system when bones are damaged, and then the BMSCs from the injured tissue and the circulatory system migrated to the damaged site and differentiate into specific tissues [22]. BMSCs are directly involved in fracture healing [23]. To further explore whether the pretreatment of LIPUS will have beneficial effects on the migration of exogenous BMSCs to the bone defect area in vivo, this study successfully established an animal femoral defect model that could simulate fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human bone morphogenetic protein (rhBMP)‐2 has been approved by the FDA for clinical applications due to its role in osteogenesis and angiogenesis during bone healing . Furthermore, it is often used in combination with seed cells such as BMSCs to maximize their capacity to accelerate osteogenesis at the site of a bone defect. However, several clinical studies of BMP‐2 have reported adverse inflammation‐related events and a low efficacy of BMP‐2 due to inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental aspects in this group of ceramics are firstly their “smart” capacity to adapt and modify their properties to the changing implant site environment, and secondly, a diverse handling method, mostly at room temperature, that allow the inclusion and preservation of bioactive molecules (drugs/antibiotics, growth factors, magnetic particles for thermal cancer therapy) ( Vallet-Regi et al, 2012 ; Comesaña et al, 2015 ; Koju et al, 2018 ; Vallet-Regí and Salinas, 2019 ). With the purpose to obtain enhanced therapeutic effectiveness, these materials were therefore tested in many studies as drug carriers or as gene delivery systems ( Ruiz-Hernández et al, 2008 ; Liu et al, 2009 ; Vallet-Regí and Ruiz-Hernández, 2011 ; Wu and Chang, 2014 ; Gao et al, 2015 ; Santos et al, 2017 ; Köse et al, 2018 ; Afewerki et al, 2020 ). To better resemble natural bone apatite and interact with neighbor tissues, synthetic HA can include several diverse ions in place of Ca 2+ , PO 4 3– , or OH – , e.g., Na + , K + , Mg 2+, Sr 2+ , Zn 2+ , Cl – , F – , HPO 4 2– ( Kim et al, 1998 ; Vallet-Regí and Arcos, 2005 ; Landi et al, 2007 , 2008 ; Kolmas et al, 2011 ; Bornapour et al, 2013 ; Montesi et al, 2017 ; Arcos and Vallet-Regí, 2020 ).…”
Section: Biomaterials For Bone Tissue Applicationsmentioning
confidence: 99%